Membangun Kerja Sama Anak Usia Dini Melalui Permainan Tradisional Gobak Sodor Di Tk Aisyiyah Raudhatul Istiqlal Setu Tangerang Selatan - Arief Rahman Muhammad; Desy Ayu Ningrum (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
This study aims to build cooperation in early childhood in Aisyiyah Raudhatul Istiqlal Kindergarten Setu South Tangerang through the traditional game of gobak sodor. This study is motivated by the importance of building cooperation in early childhood. The research method used is Classroom Action Research (CAR) with a qualitative descriptive approach, implemented in two cycles. The subjects of the study were students in group B of Aisyiyah Raudhatul Istiqlal Kindergarten Setu South Tangerang aged 5-6 years. Data collection was carried out through observation and documentation. The results of the study indicate that the traditional game of gobak sodor is effective in improving children's cooperation skills, which include the ability of children to play harmoniously, children help each other develop strategies to win, children have goals in line with their teammates, and children show mutual respect between friends. The improvement is seen from the increasing percentage of children who reach the Very Good Development (BSB) category from 9% in the pre-cycle to 87% at the end of the second cycle. It was concluded that the game of gobak sodor can be a fun and effective learning alternative to enhance cooperation in early childhood.